Human monkeypox: history, presentations, transmission, epidemiology, diagnosis, treatment, and prevention - Zahmatyar, Mahdi; Fazlollahi, Asra; Motamedi, Alireza; Zolfi, Maedeh; Seyedi, Fatemeh; Nejadghaderi, Seyed Aria; Sullman, Mark J. M.; Mohammadinasab, Reza; Kolahi, Ali-Asghar; Arshi, Shahnam; Safiri, Saeid (Frontiers in Medicine, 2023)
Human monkeypox is a zoonotic infection that is similar to the diseases caused by other poxviruses. It is endemic among wild rodents in the rainforests of Central and Western Africa, and can be transmitted via direct skin contact or mucosal exposure to infected animals. The initial symptoms include fever, headache, myalgia, fatigue, and lymphadenopathy, the last of which is the main symptom that distinguishes it from smallpox. In order to prevent and manage the disease, those who are infected must be rapidly diagnosed and isolated. Several vaccines have already been developed (e.g., JYNNEOS, ACAM2000 and ACAM3000) and antiviral drugs (e.g., cidofovir and tecovirimat) can also be used to treat the disease. In the present study, we review the history, morphology, clinical presentations, transmission routes, diagnosis, prevention, and potential treatment strategies for monkeypox, in order to enable health authorities and physicians to better deal with this emerging crisis.